For love of animals : Christian ethics, consistent action - Camosy, Charles Christopher (Cincinnati, OH : Fransicscan Media, 2013)
"For Love of Animals is an honest and thoughtful look at our responsibility as Christians with respect to animals. Many Christians misunderstand both history and their own tradition in thinking about animals. They are joined by prominent secular thinkers who blame Christianity for the Western world's failure to seriously consider the moral status of animals. This book explains how traditional Christian ideas and principles--like nonviolence, concern for the vulnerable, respect for life, stewardship of God's creation, and rejection of consumerism--require us to treat animals morally. Though this point of view is often thought of as liberal, the book cites several conservatives who are also concerned about animals. Camosy's Christian argument transcends secular politics. The book's starting point for a Christian position on animals--from the creation story in Genesis to Jesus' eating habits in the Gospels--rests in Scripture. It then moves to explore the views of the Church Fathers, the teachings of the Catholic Church, and current discussions in both Catholic and Protestant theology. Ultimately, however, the book is concerned not with abstract ideas, but with how we should live our everyday lives. Should Christians eat meat? Is cooperation with factory farming evil? What sort of medical research on animals is justified? Camosy also asks difficult questions about hunting and pet ownership. This is an ideal resource for those who are interested in thinking about animals from the perspective of Christian ethics and the consistent ethic of life. Discussion questions at the end of each chapter and suggestions for further reading round out the usefulness of this important work"--
"For Love of Animals is an honest and thoughtful look at our responsibility as Christians with respect to animals. Many Christians misunderstand both history and their own tradition in thinking about animals. They are joined by prominent secular thinkers who blame Christianity for the Western world's failure to seriously consider the moral status of animals. This book explains how traditional Christian ideas and principles--like nonviolence, concern for the vulnerable, respect for life, stewardship of God's creation, and rejection of consumerism--require us to treat animals morally"--
Includes bibliographical references.
Keywords: Animals -- Religious aspects -- Christianity; Animal welfare -- Religious aspects -- Christianity; Christian ethics